ANALYSIS OF THE EUROPEAN BANK FOR RECONSTRUCTION AND DEVELOPMENT’S FINANCING OF PROJECTS IN PRIVATE BUSINESS - AHMEDOVA NILUFAR (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
This article is devoted to the issues of effective organization of project financing through bank loans. The study analyzes the essence of project financing, the role of banks in this process, and factors that contribute to increasing efficiency. It also studies the importance of risk management, the introduction of long-term and favorable interest loans in financing projects through bank loans. Successful financing methods are shown on the example of foreign experience and the possibilities of adapting them to the conditions of Uzbekistan are suggested. The results of the article offer practical recommendations for increasing the efficiency of project financing in banks and help improve the financing process.